Spatial Segregation and Gender-Based Resource Inequality in Urban Areas: Case Study of Elite Neighborhoods and Surrounding Communities in Indonesia - Tri Budiarti, Riskha; Diansah, Irani; Nurdini, Nurdini (WISE Pendidikan Indonesia, 2024)
This study explores the impact of spatial segregation on gender-based resource inequality in urban areas of Indonesia. Through interviews, observations, and image analysis in three elite residential areas Bintaro, Kota Baru Parahyangan, and Citra Grand City, the research highlights significant inequalities in income, education, health, and access to basic services between residents of these elite areas and those in surrounding communities. The findings show that men in elite areas have better access to economic resources and job opportunities, while women in nearby communities are often disadvantaged in terms of employment and education. This gender-based inequality is worsened by the privatization of basic services like water and sanitation. The study also notes some benefits of elite area development for surrounding communities, such as improved road access. Overall, the research underscores the need to address spatial segregation and gender inequalities to achieve more inclusive urban development. Policy recommendations focus on reducing inequalities and creating a more equitable urban environment.